Reactivity of activated electrophiles and nucleophiles: labile intermediates and properties of the reaction products - Zanna, Nicola <1983> (Alma Mater Studiorum - Università di Bologna, 2013)
The main topic of my Ph.D. thesis is the study of nucleophilic and electrophilic aromatic substitution reaction, in particular from a mechanistic point of view. The research was mainly focused on the reactivity of superactivated aromatic systems. In spite of their high reactivity (hence the high reaction’s rate), we were able to identify and in some case to isolate -complexes until now only hypothesized. For example, interesting results comes from the study of the protonation of the supernucleophiles tris(dialkylamino)benzenes. However, the best result obtained in this field was the isolation and structural characterization of the first stables zwitterionic Wheland-Meisenheimer complexes by using 2,4-dipyrrolidine-1,3-thiazole as supernucleophile and 4,6-dinitrobenzofuroxan or 4,6-dinitrotetrazolepyridine as superelectrophile. These reactions were also studied by means of computational chemistry, which allowed us to better investigate on the energetic and properties of the reactions and reactants studied. We also discovered, in some case fortuitously, some relevant properties and application of the compounds we synthesized, such as fluorescence in solid state and nanoparticles, or textile dyeing. We decided to investigate all these findings also by collaborating with other research groups. During a period in the “Laboratoire de Structure et Réactivité des Systèmes Moléculaires Complexes-SRSMC, Université de Lorraine et CNRS, France, I carried out computational studies on new iron complexes for the use as dyes in Dye Sensitized Solar Cells (DSSC). Furthermore, thanks to this new expertise, I was involved in a collaboration for the study of the ligands’ interaction in biological systems. A collaboration with University of Urbino allowed us to investigate on the reactivity of 1,2-diaza-1,3-dienes toward nucleophiles such as amino and phosphine derivatives, which led to the synthesis of new products some of which are 6 or 7 member heterocycles containing both phosphorus and nitrogen atoms.